Physical Activity and Amyloid‐β Brain Levels in Elderly Adults with Intact Cognition and Mild Cognitive Impairment. Issue 8 (22nd July 2015) - de Souto Barreto, Philipe; Andrieu, Sandrine; Payoux, Pierre; Demougeot, Laurent; Rolland, Yves; Vellas, Bruno; ,
Abstract : Objectives: To examine the associations between amyloid‐ β brain deposition and physical activity (PA) in elderly adults without dementia and to investigate whether the association has a dose‐response relationship. Design: Cross‐sectional study. Setting: French community‐dwelling people. Participants: Elderly adults with normal or mildly impaired cognition (mean age 74.7 ± 4.2; 60.4% female) with available information on current self‐reported PA and amyloid‐ β brain deposition measured using positron emission tomography (PET) using the PET‐ligand florbetapir F 18 (n = 268). Measurements: A standardized uptake value ratio (SUVR) was obtained for each subject. Participants were divided according to amyloid plaque cortical retention defined according to a SUVR cutoff of 1.10 (SUVR+ vs SUVR−). Results: Bivariate and multivariate analyses showed that PA was not significantly associated with SUVR. SUVR+ and SUVR− participants did not differ in terms of volume (continuous PA variables) and levels (categorical PA variables) of PA. PA was not correlated with SUVR in apolipoprotein E ε 4 carriers or noncarriers. PA was not associated with cognitive function. Conclusion: Although PA protects against dementia, there is no solid evidence that this protection involves a reduction in amyloid‐ β brain deposition. Further studies are needed to determine whether PA (ideally measured at several time‐points using objective measures) is involved in the pathophysiology of Alzheimer's disease.